Large-scale disasters and the insurance industry - Walter Krämer; Sebastian T. Schich (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2005)
We investigate the effect of the 20 largest – in terms of insured losses – man-made or natural disasters on the insurance industry. We show via an event study that insurance markets worldwide are quite resilient to unexpected losses to capital and are even outperforming the general market subsequent to great disasters.
Keywords: 519; disaster; insurance industry; event-study; Versicherung; Naturkatastrophe; Politische Gewalt; Kapitalertrag; Schätzung; Welt